2020
DOI: 10.46253/jnacs.v3i4.a5
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Aware routing in MANET: Hybrid Genetic and Group Search Algorithm

Abstract: MANET is the infrastructure-less, self-organized wireless network. Here, the mobile nodes can join the group or leave from the network group dynamically. As the mobile ad hoc network (MANET) is established with the battery power nodes, reducing the power consumption of mobile node poses a major complex in the network system. Efficient and robust secure routing protocols are required in MANET due to the quickly changing network topology such that the overhead incurred in the track is excessive. To achieve the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…for successful floor planning with minimized cost. In literature (Beno et al 2014) [31] (Malik 2020), it has been suggested that the hybrid optimization models are good in enhancing the convergence of the solutions and thereby they aid in achieving the defined objective function. However, it's crucial to verify the predicted model's effectiveness in attaining the optimal solution specified in Eq (2).…”
Section: Convergence Analysismentioning
confidence: 99%
“…for successful floor planning with minimized cost. In literature (Beno et al 2014) [31] (Malik 2020), it has been suggested that the hybrid optimization models are good in enhancing the convergence of the solutions and thereby they aid in achieving the defined objective function. However, it's crucial to verify the predicted model's effectiveness in attaining the optimal solution specified in Eq (2).…”
Section: Convergence Analysismentioning
confidence: 99%